Effect of Milk and Hydro-priming on Seed Germination Characteristics of Bitter Gourd (Momordica charantia L.) - Md. Sadiqur Rahman; Istiak Ahmed; Suman Biswas; Monjur Morshed; Parimal Chandra Sarker; Md. Arafat Hossain; Maria Islam; Taslima Jahan (Turkish Journal of Agriculture: Food Science and Technology)
To meet the demand for an appropriate soaking duration and priming type, there is a need to embrace cheap, fast, natural, accessible, and adaptable physiological techniques as soaking of seeds in water and fresh cow milk. Fresh cow milk contains hormones that relieve seeds from photo, thermo, physiological and mechanical dormancy. In light of this, this study was conducted to assess the effect of hydration and fresh cow milk on different seed quality attributes like germination percentage, mean germination time, the uncertainty of germination process, and synchrony of germination process of bitter gourd seeds. The study involved two factors namely hydropriming and different concentrations of fresh cow milk (viz. 60%, 80% and 100%), and the other factor was seed soaking duration with 4 levels (i. e., 0, 12, 18 and 24 hours). The experiment was conducted in a Complete Randomized Design (CRD) with three replicates. Results revealed that the percentage germination value of seeds soaked in all concentrations of fresh cow milk was better than hydropriming. A significant germination percentage value of 96% and 93% were recorded for seeds treated for 18 hours in 80% and 100% concentrations of fresh cow milk respectively. Maximum uncertainty of the germination process and minimum synchrony of germination the process was recorded in untreated seed.